Analisis Pendapatan Budidaya Dan Pengolahan Hasil Gembili (Dioscorea esculenta) Sebagai Sumber Pangan Alternatif Bagi Keluarga Di Kampung Yanggandur - Tatay, Paskalina; Widiastuti, Maria Maghdalena Diana; Untari, Untari (MuJAgri: Musamus Journal of Agribusiness, 2018)
Local food which can be utilized as a source of carbohydrates is gembili (Dioscorea esculenta). The farming system of gembili stil in tradisonial way and not for the profit oriented. Meanwhile the nutrition of gembili almost the same as other carbohydrates such as rice or sweet potatoes. The purpose of this research is to analyze cost and benefit of gembili cultivation and processing of gembili become donut and cake gembili. The methodology using Benefit Cost Ratio (B/C Ratio) and Revenue Cost Ratio (R/C Ratio). This research was conducted in December 2017 to January 2018 in Kampung Yanggandur District Sota Merauke Regency. Sampling technique used Snowball Sampling. The samples are 7 respondents. The results showed that the cost of farming cultivation gembili is Rp44.871.140, -, while the benefit is Rp86.225.040, - The profit gain as Rp41.353.900,-. The B/C Ratio is 1,92. Gembili procesing become cake gembili more profitable than donut gembili. The cost of donut gembili is Rp5.582.000/month, while the cake gembili is Rp4.804.000/month. The revenue of donut gembili is Rp7.200.000/monthwhile the renenue of cake gembili is Rp15.000.000,00/month. The R/C Ratio of donut gembili is 0.53 while cake gembili is 1,69 means both of gembili processing become donut dand cake gembili is feasible to developed. Keywords: cost, benefit, feasibility, gembili.